2010
DOI: 10.1038/onc.2010.203
|View full text |Cite
|
Sign up to set email alerts
|

TLR9 triggering in Burkitt's lymphoma cell lines suppresses the EBV BZLF1 transcription via histone modification

Abstract: Endemic Burkitt's lymphoma (BL) is considered to preferentially develop in equatorial Africa because of chronic co-infection with Epstein-Barr virus (EBV) and the malaria pathogen Plasmodium falciparum. The interaction and contribution of both pathogens in the oncogenic process are poorly understood. Earlier, we showed that immune activation with a synthetic Toll-like receptor 9 (TLR9) ligand suppresses the initiation of EBV lytic replication in primary human B cells. In this study we investigate the mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 43 publications
4
38
0
Order By: Relevance
“…2A). It seems likely that this feature is shared by other gammaherpesviruses, as previous studies in our laboratory demonstrated that stimulation of TLR9 similarly leads to a suppression of EBV's master regulator lytic BZLF1 gene in Burkitt's lymphoma cells (8,9). Our finding that signaling via TLR7 suppresses MHV 68 reactivation is unprecedented.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…2A). It seems likely that this feature is shared by other gammaherpesviruses, as previous studies in our laboratory demonstrated that stimulation of TLR9 similarly leads to a suppression of EBV's master regulator lytic BZLF1 gene in Burkitt's lymphoma cells (8,9). Our finding that signaling via TLR7 suppresses MHV 68 reactivation is unprecedented.…”
Section: Discussionsupporting
confidence: 55%
“…Indeed, with respect to EBV-associated B-cell malignancies, P. falciparum malaria is epidemiologically associated with endemic BL, and the parasite was reported to directly stimulate TLR9 (11,12). Earlier we showed that P. falciparum hemozoin suppresses lytic reactivation of EBV in BL cells (9), further underscoring activation of TLR signaling pathways as a possible mechanistic link between chronic malaria infection and the incidence of endemic BL. The situation in KSHV-associated primary effusion lymphoma, however, may be distinct, as suggested by the lytic reactivation of KSHV following triggering of TLR7/8 (7).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the case of endemic Burkitt's lymphoma, TLR9 may play a role in the survival of the malignant B cells by preventing the lytic phase of the Epstein-Barr virus [82]. Activation of TLR9 causes decreased levels of phosphorylated histone H3 and acetylated histones H4 and H3 bound to the Epstein-Barr virus master regulatory lytic gene promoter, thus preventing the virus from entering the lytic phase [82].…”
Section: Toll-like Receptors and The Governing Epigenetic Mechanisms:mentioning
confidence: 99%
“…TLRs 3,7,8, and 9 were demonstrated to recognize different forms of microbial-derived nucleic acid. TLR9 detects unmethylated CpG motifs found in the genomic DNA from a variety of viruses, such as EBV, human papillomavirus type 16 (HPV16), and HSV-2 (1)(2)(3)(4)(5). Although TLR9 signaling in hematopoietic cells was demonstrated to control infection of several DNA viruses, TLR9 is also expressed on epithelial cells, such as keratinocytes (6)(7)(8).…”
mentioning
confidence: 99%